2019
DOI: 10.3390/jcm8101694
|View full text |Cite
|
Sign up to set email alerts
|

ICSI versus Conventional IVF in Women Aged 40 Years or More and Unexplained Infertility: A Retrospective Evaluation of 685 Cycles with Propensity Score Model

Abstract: This study compared the cumulative live birth rates following Intracytoplasmic sperm injection (ICSI) versus conventional in vitro fertilization (cIVF) in women aged 40 years or more and unexplained infertility. A cohort of 685 women undergoing either autologous conventional IVF or ICSI was retrospectively analyzed. The effects of conventional IVF or ICSI procedure on cumulative pregnancy and live birth rates were evaluated in univariate and in multivariable analysis. In order to reduce potential differences b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 42 publications
(53 reference statements)
0
21
0
Order By: Relevance
“…Large studies comparing the results of cIVF and ICSI for the treatment of non-male factor infertility showed quite clearly that ICSI cannot offer any advantage in terms of clinical outcome [19][20][21]. Nevertheless, data showing that ovarian endometriosis negatively affects oocyte quality [8][9][10] led to the idea that using ICSI instead of cIVF could be advantageous for this specific subset of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Large studies comparing the results of cIVF and ICSI for the treatment of non-male factor infertility showed quite clearly that ICSI cannot offer any advantage in terms of clinical outcome [19][20][21]. Nevertheless, data showing that ovarian endometriosis negatively affects oocyte quality [8][9][10] led to the idea that using ICSI instead of cIVF could be advantageous for this specific subset of patients.…”
Section: Discussionmentioning
confidence: 99%
“…6 While ICSI has resulted in high success rates in couples treated for severe male factor infertility, studies have indicated that ICSI offers no advantage over conventional IVF in nonmale factor infertility couples when it comes to live birth rates. [7][8][9][10][11] Moreover, the American Society for Reproductive Medicine recently published a committee opinion stating that 'in cases without male factor infertility or a history of prior fertilisation failure, the routine use of ICSI for all oocytes is not supported by the available evidence'. 12 In the US study from 2018, the large increase in use of ICSI was correlated with a 7.6% (p=0.001) increase in live birth rates per cycle in women younger than 35 years.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Conventional IVF is known as an effective technique for fertilization and successful embryo development in case of non-male infertility factors. Several studies have shown that conventional IVF is a better approach than ICSI when sperm concentration, motility and morphology are normal (Bhattacharya et al, 2001;Gennarelli et al, 2019;Stimpfel et al, 2019). During the conventional IVF process, ROS can originate from dead spermatozoa and white blood cells of sperm.…”
Section: Oxidative Stress In Assisted Reproduction Techniques (Art)mentioning
confidence: 99%
“…ICSI was designed to overcome unexplained infertility, poor quality embryo retrieval, advanced maternal age, severe form of male infertility, (Feldman et al, 2017), fertilization after in vitro maturation and fertilization of frozen-thawed oocytes (Luna et al, 2011; Practice Committees of the American Society for Reproductive Medicine and Society for Assisted Reproductive Technology, 2012; Tannus et al, 2017). In this way, ICSI is an efficient technique that can prevent 30% of fertilization failures (Tournaye et al, 2002;Gennarelli et al, 2019). During ICSI procedures, cumulus cell removal can deprive oocytes from protection against irreversible oxidative damage, during maturation and fertilization.…”
Section: Oxidative Stress In Assisted Reproduction Techniques (Art)mentioning
confidence: 99%